Constant light and high fat diet alter daily patterns of activity, feed intake and fecal corticosterone levels in pregnant and lactating female ICR mice. - Leriana Garcia Reis; Kelsey Teeple; Jenna Lynn Schoonmaker; Corrin Davis; Sara Scinto; Allan Schinckel; Theresa Casey (PLoS ONE)
The prevalence of constant light exposure and high-fat diet in modern society raises concerns regarding their impact on maternal and offspring health outcomes. In rodents, exposure to maternal high-fat diet or continuous light negatively program metabolic and stress response outcomes of offspring. A 2x3 factorial study was conducted to investigate the impact of diet (control-CON, 10% fat, or high fat-HF, 60% fat) and exposure to different lighting conditions: regular 12-hour light-dark cycles (LD), continuous dim light (L5), or continuous bright light (L100) on female ICR mice daily patterns of time in and out of the nest, feed intake, and fecal corticosterone levels during gestation and lactation. Our previous analysis of these mice found HF diet decreased number of pups born, but increased litter growth rate to postnatal (PN) d12. Whereas continuous light increased gestation length and tended to increase PN litter growth. Here we report that patterns of grams of feed intake, an indicator of feeding activity, were affected by light, diet, period of the day (day versus night) and physiological state (gestation and lactation), with significant interactions among all these variables (P<0.05). HF diet and light treatment increased fecal corticosterone output (P<0.05) during lactation. Dams exhibited significant 12 h and 24 h rhythms of activity out of the nest in the first 48 h postnatal, with time outside of the nest greater in the second 24 h period. L100 treatment and HF diet attenuated rhythms and shifted phase of rhythms relative to LD and CON, respectively (P<0.05). Alterations in behavior affect maternal physiology, including level and timing of release of corticosteroids. Elevated fecal corticosterone levels due to high-fat diet and continuous light may have potential implications on maternal-offspring health, and potentially underlie some of the adverse effects of modern lifestyle factors on maternal and offspring health.